Novel Circovirus from Mink, China - Hai Lian; Ye Liu; Nan Li; Yuying Wang; Shoufeng Zhang; Rongliang Hu (Emerging Infectious Diseases, 2014)
A long-established epidemic of enteritis, caused by an unidentified pathogen distinct from parvovirus, has now been recognized in mink. In 2013, we identified a novel circovirus by degenerate PCR and fully sequenced its genome. This virus differs substantially from currently known members of the genus Circovirus and represents a new species.